Masterpieces of Korean art Lee Kyong-hee ; copy editor Teresita M. Reed]. - Lee, Kyong-hee 1947-.; Reed, Teresita M.; Korea Foundation (Seoul). (Seoul Korea Foundation, 2010)
Arts, Korean.
Compilation of articles from Koreana magazine, 2000-2010.
Keywords: Art, Korean -- Catalogs